A Educação de jovens e adultos em privação de liberdade : um estudo da universidade prisional de Goianésia-GO - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The current research has as a general goal to analyse if the undertaken educational practices in the Prison Unity in Goianésia- GO have been able to articulate a compatible education with the social reintegration proposal of the arrested subjects. Specifically, it is proposed to identify which are the used practices in the Prison Unity and if they match with the idea of reintegration; to identify the profiles of the arrested subjects in Goianésia, to analyse the concepts which these students have about education, as well as to analyse if the subjects involved in the research realize the education as the social reintegration factor. The study object is composed by three elements, namely: educational practice, prison unity and social reintegration. The methodological choice was the qualitative research according to Lüdke and André's assumptions (1986), with the usage of several instruments to collect the data, such as the Prison Unity and school characterization chart, the semi structured interview script, register protocols and the field diary. To conduct the study, ti was used Minayo's (2013) research cycle which led to meaningful results and allowed new questions. As theoretical framework in order to understand the study object and for subsidy in the analysis of the categories, some authors were resorted such as Libâneo (1999, 2003, 2012, 2015) Brandão (1995), Freire (1996), Saviani (2001), Candau (1990), Zabala (1998), Adorno (1995, 2008), Gadotti (2000), Julião (2007, 2011), Goffman (2010), Onofre (2007, 2012), Silva (2007), Foucalt (1999a, 1999b), Wacquant (2001), Goffman (2010), Durkheim (1999, 2001), Marx (1996a, 1996b), Weber (2004), Paiva (2011), Fávero (2011), Vygotsky (1991) and others. The data analyses was according to Franco's guidances (2012), in which were elaborated the analysis categories, which are: 1) school and knowledge; 2) pedagogical practices and teacher-student relation and 3) education, change and social reintegration. The three categories themselves articulate and evidence the importance of the teaching of the meaningful and systematized content mediated by effective pedagogical practices which, lead to knowledge in a dialogic and respectful way. They have the intention of ensuring the autonomous thought formation and enabling the emancipatory perspectives, in view of, the educative practice in this work, it is understood as intentional and political. The study emphasizes all the limits of education for a change, in a disciplinarian and repressive space; however, it reveals that, the Prison Unity teachers and students in Goianésia, perceive that the offered education in prison is according to a social reintegration proposal, offering conditions so that the subjects deprived of freedom can be reinserted in the society in a more reflexive way, from the acquired knowledge.
Keywords: Práticas educativas em escola prisional; Unidade prisional e educação; Educação e reinserção social; Educational practices inthe prision school; Prision unity an education; EDucation and social reintegration; CIENCIAS HUMANAS::EDUCACAO